Pericarp-mediated chemical dormancy controls the fruit germination of the invasive hoary cress (Lepidium draba), but not of hairy whitetop (Lepidium appelianum). Issue 5 (8th July 2019) - Mohammed, Said; Turečková, Veronika; Tarkowská, Danuše; Strnad, Miroslav; Mummenhoff, Klaus; Leubner-Metzger, Gerhard
Abstract: This study provides a comparative analysis of the dormancy and germination mechanisms of the indehiscent fruits of hoary cress ( Lepidium draba L.) and hairy whitetop ( Lepidium appelianum Al-Shehbaz), two invasive weeds of the Brassicaceae. Germination assays comparing isolated seeds (manually removed from the fruits) and intact indehiscent fruits showed that the isolated seeds are nondormant and provided full germination for both species. In contrast to this, the species differed in the germination properties of their indehiscent fruits, in that L. appelianum fruits were nondormant, while the L. draba fruit coat (pericarp) conferred a coat-imposed dormancy. The pericarp of L. draba fresh fruit was water permeable, and neither mechanical scarification nor surface sterilization affected germination, supporting the concept that pericarp-mediated dormancy was not due to water impermeability or mechanical constraint. Washing of L. draba fruits with water, afterripening (dry storage), and treatment with gibberellin (GA) stimulated the germination of this species, all of which are indicative of physiological dormancy. Analyses of endogenous abscisic acid (ABA) and GA levels combined with treatment experiments with wash water from fresh and afterripened L. draba pericarps and with ABA dose–response quantification of germination revealed that ABA is a key component of a pericarp-mediated chemical dormancy in this species. Consistent with this, pericarp ABA levels decreased during afterripening and upon fruit washing, and isolated fresh or afterripened seeds did not differ in their ABA sensitivities. The possible roles of the ABA-mediated pericarp dormancy for the germination ecophysiology and weed management of these species are discussed.